Physicochemical studies of mild steel corrosion and atmospheric corrosivity mapping of Karachi: An important harbor city of modern Maritime Silk Route. Issue 9 (2nd June 2020) - Zafar, Faiza; Bano, Humaira; Mahmood, Azhar; Corvo, Francisco; Rodriguez, Joelis
Abstract: This paper has reported physicochemical features of mild steel's corrosion products and provided atmospheric corrosivity maps of Karachi harbor city, drafted on the basis of spatial distribution of corrosion data from July 2018 to June 2019 at 10 different urban, industrial, and marine test sites. Exposure tests have been performed to study atmospheric corrosivity, corrosion products, and corrodants including chloride, sulfur dioxide, time of wetness (TOW), and corrosion rate as per ISO and ASTM standards. Scanning electron microscope, Fourier‐transform infrared spectroscopy, and X‐ray diffraction have corroborated the presence of lepidocrocite, goethite, magnetite, and quartz phases at almost all the test sites, with slight variations in their morphologies and quantities. The data analysis has revealed that TOW is a major detrimental factor to accelerate corrosion of mild steel at Karachi city. The corrosivity category of all urban and marine test sites is found in C4 –C5 range, whereas for industrial test sites, it is found in C3 –C5 range. Resultant corrosivity maps have shown that the prevailing atmosphere is significantly corrosive at Karachi harbor city. This study has furnished a novel product of atmospheric corrosivity map, which is the first‐ever corrosivity map for Pakistan. Abstract : This study has furnished the first‐ever atmospheric corrosivity map of Karachi city, an important harbor city of the modern Maritime Silk Route and a key part of China Pakistan Economic Corridor, by employing ASTM and ISO standards, which complement spectroscopic techniques. The corrosion data analysis has revealed that the time of wetness is a major detrimental factor to accelerate corrosion at Karachi city.